Shh agonist enhances maturation in homotypic Lgr5-positive inner ear organoids - Carpena, Nathaniel T.; Chang, So Young; Mun, Seyoung; Kim, Kyung Wook; Yoon, Hyun C.; Chung, Phil Sang; Mo, Ji Hun; Ahn, Jin Chul; Park, Ji On; Han, Kyudong; Choi, Ji Eun; Jung, Jae Yun; et al. (Theranostics, 2025)
Background: The regeneration of functional hair cells (HCs) remains a critical challenge in addressing sensorineural hearing loss. This study aimed to investigate the molecular and functional mechanisms driving stereocilia maturation within inner ear organoids (IEO) derived from homogenic Lgr5-positive progenitor cells (LPCs) and to compare outcomes with traditional heterotypic cultures. Methods: Mouse cochlear LPCs were isolated via magnetic-activated cell sorting (MACS) to establish homotypic cultures, ensuring purity and eliminating the heterotypic influences present in traditional manual isolation (MI) methods. Differentiation into HCs was induced through Wnt and Notch signaling modulation. Transcriptomic profiling using bulk and single-cell RNA sequencing (scRNA-seq) identified gene expression changes linked to stereocilia development. A Sonic Hedgehog (Shh) agonist was applied to enhance structural maturation of HCs. Functional assessment included electron microscopy, FM1-43 uptake assays, and microelectrode array recordings in assembloids of IEO with primary spiral ganglion neurons (SGN) co-cultures. Results: While homotypic LPC-derived IEOs successfully differentiated into HC-like cells, initial morphological assessment revealed immature stereocilia structures. Bulk RNA-seq analysis highlighted a downregulation of morphogenesis-related genes in these organoids. The application of a Shh agonist, acting as a key morphogen, promoted stereocilia development, as evidenced by enhanced ultrastructural features and increased expression of cuticular plate-associated genes (Pls1, Lmo7 and Lrba). Single-cell RNA sequencing (scRNA-seq) further identified distinct cell clusters, which exhibited robust expression of stereocilia-related genes (Espn, Lhfpl5, Loxhd1 and Tmc1), indicative of advanced HC maturation. Electrophysiological assessments of IEO-SGN assembloids using microelectrode arrays confirmed functional mechanoelectrical transduction between cells. Conclusion: This integrated approach elucidates critical pathways and cellular dynamics underpinning stereocilia maturation and functional HC development in EIOs. These findings provide new insights into the molecular regulation of HC maturation and support the utility of Shh-modulated IEOs as a promising platform for inner ear regeneration and therapeutic development for inner ear regenerative therapies.
Keywords: Animals; Cell Differentiation; Coculture Techniques; Ear, Inner; Hair Cells, Auditory; Hedgehog Proteins; Mice; Mice, Inbred C57BL; Organoids; Receptors, G-Protein-Coupled; Spiral Ganglion; Stem Cells; Stereocilia; inner ear organoid; Lgr5; microelectrode array; RNA sequencing; sonic hedgehog